Standard specification for nickel plate, sheet, and strip
This specification2 covers rolled nickel (UNS N02200) and low-carbon nickel (UNS N02201)* plate, sheet, and strip. This standard does not purport to address all of the safety concerns, if any, associated with its use. It is the responsibility of the user of this standard to become familiar with all hazards including those identified in the appropriate Material Safety Data Sheet (MSDS) for this product/material as provided by the manufacturer, to establish appropriate safety and health practices, and determine the applicability of regulatory limitations prior to use.